The Effects of Water Debit and Number of Blades on the Power Generated of Prototype Turbines Propeller as Renewable Electricity - Biantoro, Agung Wahyudi; Iskendar, Iskendar; Subekti, Subekti; bin Muhd Noor, Nik Hisyamudin (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
This research is a prototype design of a Pico hydropower plant. The Pico hydro laboratory scale is planned to be installed at the water outlet at the steam gas power plant (PLTGU) in Cilegon, whose water discharge has not been utilized. Pico hydro will produce green energy, which in turn can partially replace fossil energy needs. The purpose of this study was to determine the effect of water discharge and the number of blades on the power generated by Pico hydro. The method used in this research is an experimental method carried out in the laboratory, by designing and making Pico hydro prototypes, with several variations in the number of blades. The results of the manual calculation analysis show that the mass flow rate, circumferential speed, and the highest rotational speed are found in blade 6. Furthermore, the design process uses the CFD method, which produces the best energy when using 6 or 7 blades.Â The stronger the water discharge, the higher the Rpm, and the stronger the electric current and the resulting voltage. The water discharge of 0.04 m3/s produces 215 Rpm, a current of 0.30 ampere, and a voltage of 2.00 volts. While the airflow rate of 0.08 m3/s produces 695 Rpm, a current of 0.70 ampere,s and a voltage of 4.30 volts. Statistical analysis also shows that the higher the Rpm value of the 6 blade turbine, the higher the power and current it produces.